Nanozdravila za lokalno zdravljenje parodontalne bolezni - Zupančič, Špela (Farmacevtski vestnik, 2016)
Periodontal disease is a chronic inflammation of periodontal tissues resulting in destruction of the periodontal ligament, root cementum, and alveolar bone, formation of periodontal pockets and teeth loss. In numerous cases, the treatment according to the current guidelines does not lead to the desired outcome, and consequently, new approaches and medicines are under development. In this review article, different possible approaches are presented, which are (I) reduction of pathogen bacteria and establishment of a nor- mal oral flora, (II) host modulation therapy, and (III) improvement of tissue regeneration mostly with nanomedicines, such as liposomes, nanopar ticles, and nanofibers loaded with a drug. Nanomedicines can enable prolonged retention and controlled drug release at the targeted site; moreover, nanofibers can also increase periodontal disease regeneration.
Keywords: antibiotic; antibiotiki; nanodelci; nanodostavni sistemi; nanovlakna; parodontalna bolezen; Parodontalne bolezni